Healthful housing : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Sociology at Massey University - Lynch, Kathleen (Massey University, 1999)
This study researched the housing needs of incipiently homeless low-income households in Auckland. In particular it examined how the compromises and sacrifices low-income households must make to procure housing jeopardises their ability to promote and maintain health. Health within this study was defined holisticly including physical, mental, spiritual and family aspects as well as the dimension of ontological security. The participants were comprised of three groups: housing workers, community health workers, and most importantly the households in housing need. All participants were or had been connected with Monte Cecilia Emergency House. The role of the state, past and present, in assisting low-income households to obtain accommodation was examined. Particular consideration was given to changes which have occurred in the lost-cost rental sector through the move to market-level rents for state housing, and the introduction of a targeted, abatable accommodation allowance. The participants' stories demonstrated an increasing and serious level of unaffordability of rental housing. This had brought about both immediate and long-term detriments to health due to living in over-crowded accommodation and / or a residual post-rent income insufficient to maintain an adequate standard of living. Tangata Whenua and Tagata Pasifika were disproportionately affected by unaffordable housing. The need for a return to income-related state housing was high-lighted. Recommendation was also made regarding the urgent need of a comprehensive survey of housing need, both urban and rural.
Keywords: Housing and health; Public housing; Housing policy; Emergency housing; Shelters for the homeless; Auckland; New Zealand